2020
DOI: 10.7554/elife.53868
|View full text |Cite
|
Sign up to set email alerts
|

RNA-guided retargeting of Sleeping Beauty transposition in human cells

Abstract: An ideal tool for gene therapy would enable efficient gene integration at predetermined sites in the human genome. Here we demonstrate biased genome-wide integration of the Sleeping Beauty (SB) transposon by combining it with components of the CRISPR/Cas9 system. We provide proof-of-concept that it is possible to influence the target site selection of SB by fusing it to a catalytically inactive Cas9 (dCas9) and by providing a single guide RNA (sgRNA) against the human Alu retrotransposon. Enrichment of transpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 93 publications
0
32
0
Order By: Relevance
“…The DSB induced by the sequence-specific nucleases at the target sites are fatal in organisms without effective NHEJ or HDR (Xu et al, 2015 ). To overcome this limitation, researchers attempted to connect different transposases to catalytically inactivated dCas9 (site-specific mutations were introduced into the HNH and RuvC domains to abrogate the cleavage activity without affecting the targeted binding effect) to obtain a series of dCas9–transposase fusion proteins [such as dCas9- Himar1 (Chen and Wang, 2019 ), dCas9- piggyBac (Hew et al, 2019 ), and dCas9- Sleeping Beauty (Kovač et al, 2020 )]. These fusions limit the random insertion of transposase, so that transposition occurs only near the point where dCas9 is targeted.…”
Section: Targeting Dsdna By the Type V Familymentioning
confidence: 99%
“…The DSB induced by the sequence-specific nucleases at the target sites are fatal in organisms without effective NHEJ or HDR (Xu et al, 2015 ). To overcome this limitation, researchers attempted to connect different transposases to catalytically inactivated dCas9 (site-specific mutations were introduced into the HNH and RuvC domains to abrogate the cleavage activity without affecting the targeted binding effect) to obtain a series of dCas9–transposase fusion proteins [such as dCas9- Himar1 (Chen and Wang, 2019 ), dCas9- piggyBac (Hew et al, 2019 ), and dCas9- Sleeping Beauty (Kovač et al, 2020 )]. These fusions limit the random insertion of transposase, so that transposition occurs only near the point where dCas9 is targeted.…”
Section: Targeting Dsdna By the Type V Familymentioning
confidence: 99%
“…Cas9 is a dual RNA-guided DNA endonuclease enzyme that uses base pairing to recognise and cleave target DNA with complementarity to the guide RNA, such as invading bacteriophage DNA or plasmid DNA [ 62 ]. Tethering the transposase toward a target that is overexpressed in the human genome dramatically increases the number of possible attach points and thus induces chances of targeted transposition with a flexible and easy-to-use RNA-guided system [ 63 ]. Pilot studies have indicated that SB is a safe and effective tool to manufacture therapeutic CAR-T cells in cancers [ 64 , 65 , 66 , 67 ].…”
Section: How Are Cars Engineered?mentioning
confidence: 99%
“…Targeted transposition was successful in a bacterial context [ 112 , 113 ], but still remains challenging in eukaryotic cells. By using the CRISPR/Cas9 system with its high targeting efficiency [ 114 ], SB100X transposase fused with catalytically inactive Cas9 (dCas9), and single guide RNAs (sgRNAs) targeting the human Alu retrotransposon, a slight bias towards integration with Alu elements could be accomplished in human cells [ 115 ]. However, the efficiency of the targeted transposition events remained low and further studies are required to bias SB integrations towards defined target regions.…”
Section: New Sleeping Beauty Variants Offeringmentioning
confidence: 99%